1999
DOI: 10.1002/ps.2780550202
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of famoxadone

Abstract: Famoxadone is a preventative and curative fungicide recently developed for plant disease control. The molecule and its oxazolidinone analogs (OADs) are potent inhibitors of mitochondrial electron transport, speciücally inhibiting the function of the enzyme ubiquinol :cytochrome c oxidoreductase (cytochrome Visible absorbance spectral studies on the puriüed enzyme suggested that bc 1 ). famoxadone bound close to the low potential heme of cytochrome b. This binding mode was conürmed in competitive binding experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 18 publications
0
37
1
Order By: Relevance
“…It was thus necessary to determine how pyrimorph interferes with bc 1 function at the Q P site. Since spectral changes, especially red shifts in the α- and β-band caused by binding of inhibitors to reduced bc 1 , were successfully used to deduce information about their binding interactions [37], [40], a similar approach was taken for pyrimorph. By comparing the spectra of reduced bc 1 bound with pyrimorph to those obtained with known Q P or Q N site inhibitors such as myxothiazol or antimycin A, we hoped to gain insight into the binding interactions and location.…”
Section: Resultsmentioning
confidence: 99%
“…It was thus necessary to determine how pyrimorph interferes with bc 1 function at the Q P site. Since spectral changes, especially red shifts in the α- and β-band caused by binding of inhibitors to reduced bc 1 , were successfully used to deduce information about their binding interactions [37], [40], a similar approach was taken for pyrimorph. By comparing the spectra of reduced bc 1 bound with pyrimorph to those obtained with known Q P or Q N site inhibitors such as myxothiazol or antimycin A, we hoped to gain insight into the binding interactions and location.…”
Section: Resultsmentioning
confidence: 99%
“…Initial concepts of whether a Q P inhibitor increases the redox potential of Fe 2 S 2 and/or changes the optical spectrum of the b L -heme were useful for instance in drawing attention to a connection between two prosthetic groups through the Q P site, it could not reveal nor make predictions about the motion of ISP-ED that depends on the inhibitor type [32]. For instance, famoxadone was assigned to the group of strobilurin and myxothiazol-like inhibitors [33] but in fact rather belongs to the group of stigmatellin-like inhibitors [27, 28, 34]. An increasing body of structural evidence starting with the first structures of bc 1 [13] followed by a number of high resolution inhibitor bound bc 1 complexes suggested that the influence of the inhibitor on the mobility of the ISP-ED was systematic.…”
Section: Structural Characterization Of Complex III With and Withomentioning
confidence: 99%
“…It was discovered through a chemical scouting program based on the lead compound of 5-methyl-5-phenyl-3-phenyl-amino-2-thioxo-4-oxazolidinone [33, 48, 49] and its new structure that included a chiral toxophore with a more active S(−) enantiomer [49] suggested a novel mode of action [50]. The crystal structure of bc 1 bound with famoxadone [51] revealed that famoxadone (Fig.…”
Section: Binding Mode Of Qp Site Inhibitorsmentioning
confidence: 99%
“…Strobilurin A is a natural product found in certain micro-organisms [15]. As documented, famoxadone [Famoxate@, DPX-JE874 or 5-methyl-5-(4-phenoxypheny1)-3 -phenylamino-2,4-oxazolidinedione] was optimized as a fungicide for crop protection from the initial greenhouse-active molecule 1 (see Figure 1) [10,11,13]. Famoxadone's parent, 1, was obtained from a collection of similar molecules that were primarily of synthetic interest around the heterocycles [16-231.…”
Section: Introductionmentioning
confidence: 99%
“…extended and expanded upon to clearly assign famoxadone's fungicidal properties to its Q,-site inhibition of cytochrome bc, function [lo]. Single amino acid changes in the apocytochrome b of baker's yeast cytochrome b, located within the Q, site of the enzyme, alter the IC,, values for the inhibitors famoxadone, myxothiazol (a naturalproduct Q,-site inhibitor [14]), azoxystrobin and kresoxim-methyl differentially, thus strongly suggesting differences in binding interactions of the protein among the inhibitors [10,11]. T h e possibility of understanding the binding mode of the individual Q,-site inhibitors at near-atomic resolution is encouraged from the recently reported X-ray structures of cytochrome bc, [24,25].…”
Section: Introductionmentioning
confidence: 99%